2010
DOI: 10.1016/j.jsr.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of daylight saving time on vehicle crashes in Minnesota

Abstract: Daylight saving time can lead to fewer crashes on roads by providing better visibility for drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
4
20
1
Order By: Relevance
“…Known risk factors in fatal crashes that could interact with the injury host, the agent, or the driving environment include alcohol use [27], drug use [28], poor driving record [29], no restraint use [30], high speed [31], and poor light conditions [3234]. In our analysis, alcohol or drug use, poor driving record, no restraint use, and speeding were less likely to co-occur in fatalities during adverse weather conditions suggesting the importance of adverse weather as an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Known risk factors in fatal crashes that could interact with the injury host, the agent, or the driving environment include alcohol use [27], drug use [28], poor driving record [29], no restraint use [30], high speed [31], and poor light conditions [3234]. In our analysis, alcohol or drug use, poor driving record, no restraint use, and speeding were less likely to co-occur in fatalities during adverse weather conditions suggesting the importance of adverse weather as an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…They also argued that the rate of traffic crashes was reduced because drivers may improve their driving behaviors by reducing immediate braking or speeding in response to gasoline price increases. Similarly, Huang and Levinson (2010) found that higher gasoline prices reduced traffic levels and reduced traffic diminished the number of total crashes from 2001 to 2007 in Minnesota. In addition, Chi et al (2012) found that higher gasoline prices reduced traffic crashes per capita from 1999 to 2009 in Alabama.…”
Section: Prior Researchmentioning
confidence: 93%
“…In this study, we controlled for the four categories of variables. First, VMT is an important variable to explain the variation of crashes on the road; higher VMT is always associated with more crashes (Huang and Levinson, 2010). We used VMT estimates by county and month in this study.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects tend to be stronger on younger drivers than on older drivers, on female drivers than on male drivers, and on white drivers than on black drivers (Chi et al, 2010(Chi et al, , 2012Grabowski and Morrisey, 2004;Leigh and Wilkinson, 1991). Second, gasoline prices affect different types of traffic crashes such as fatal crashes, injury crashes, property-damage-only crashes, and drunk-driving crashes differently (Chi et al, 2011;Huang and Levinson, 2010). When compared to the effects on overall crashes, gasoline prices are found to have more significant effects on less severe crashes but less significant effects on drunkdriving crashes.…”
Section: Prior Research Of Gasoline Price Effects On Traffic Safetymentioning
confidence: 99%